PENGARUH ASET PAJAK TANGGUHAN, DISCRETIONARY ACCRUAL, LEVERAGE, UKURAN PERUSAHAAN, DAN PERENCANAAN PAJAK TERHADAP PRAKTIK MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2015)
This study aims to analyze and provide empirical evidence of the influence of deferred tax asset, discretionary accrual, leverage, company size, and tax planning to the earnings management. This research uses secondary data got from annual report published in www.idx.co.id and data from Indonesian Capital Market Directory (ICMD). Populations of the research are manufacturing companies listed on Indonesia Stock Exchange from 2011-2013. Samples were selected by using purposive sampling method. There are 208 observations that will examined by logistic regression analysis. The result shows that deferred tax asset have negative and not significant effect to the earnings management, discretionary accrual have negative and not significant effect to the earnings management, leverage have negative and significant effect to the earnings management, company size have positive and significant effect to the earnings management, tax planning have positive and not significant effect to the earnings management. Keywords: Deferred Tax Asset, Discretionary Accrual, Leverage, Company Size, Tax Planning, and Earnings Management